Population Monotonicity in Newsvendor Games - Chen, Xin; Gao, Xiangyu; Hu, Zhenyu; Wang, Qiong (Management Science, 2019)
A newsvendor game allows the players to collaborate on inventory pooling and share the resulting total cost. There are several possible ways to allocate the cost. Previous studies have focused on t...